THE EXPRESSION LEVELS OF microRNAs ASSOCIATED WITH T AND B CELL DIFFERENTIATION/STIMULATION IN ANKYLOSING SPONDYLITIS - ATA, PINAR (MACEDONIAN ACAD SCIENCES ARTS, 2020)
Spondyloarthropathies (SpAs), are a group of chronic inflammatory diseases with a number of genetic, physiopathological, clinical and radiological features. Ankylosing spondylitis (AS) is the most common type of spondylo-arthropathies, and >90.0% of patients with ankylosing spondylitis are human leukocyte antigen-B27 (HLA-B27)-positive. In recent years, non-HLA genetic factors have been reported to have an effect on ankylosing spondylitis. MicroRNAs (miRNAs), are endogenous non coding RNA molecules containing 18-23 nucleotides that play a role in the post-transcriptional regulation of gene expression. In this study, we aimed to determine the expression levels of miRNAs associated with T- and B-cell differentiation/ stimulation in peripheral blood mononuclear cells and their relationship with the etiology of the AS in patients and healthy controls. In a molecular study, peripheral blood mononuclear cell isolation, and total RNA isolation were performed first. In the second step, cDNA synthesis and quantitative real-time PCR (qPCR) expression analysis were completed. Ultimately, in the patient and control group, the expression levels of miR-142-5p and miR-143 were found to be significantly different (p <0.05). According to current knowledge, miR-142-5p and miR-143 expressions were found to be important for those diseases that share similar etiology with AS. We suggest that miR-142-5p and miR-143 may play a role in the pathogenesis, especially miR-142-5p may be a potential biomarker and a target molecule for the treatment.
Keywords: Ankylosing spondylitis (AS); Expression level of microRNA (miRNA); miR-142-5p; miR-143; CONTRIBUTES; HLA-B27